Influence of Brand Awareness, Social Media Marketing, WOM on Onemed Purchase Decisions - Vincentia, Vania Michelle (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyse the influence of brand awareness, social media marketing, and word of mouth on purchasing decisions for OneMed Antiseptic products, with a focus on students and medical personnel in Surabaya. The increased use of antiseptics during the COVID-19 pandemic is thought to influence purchasing decisions for this product. This study examined 120 respondents consisting of medical students, doctors, nurses, and pharmacists who have purchased and used Antiseptic OneMed products. The data analysis technique used Structural Equation Modelling (SEM) with the help of SmartPLS. The results show that brand awareness and social media marketing have no significant effect on purchasing decisions, while word of mouth has a significant effect. Brand awareness also has a significant effect on word of mouth, but social media marketing does not have a significant effect. In addition, word of mouth plays an important role in mediating the effect of brand awareness on purchasing decisions, but social media marketing does not significantly influence purchasing decisions through word of mouth. This research provides insight into the factors that influence purchasing decisions for OneMed Antiseptic products, particularly in the context of a pandemic.